Synthesis of Si-MCM-41 from ternary SiO2-CTAOH-H2O system via dry gel conversion route - Taralkar, U. S.; Niphadkar, P. S.; Joshi, P. N. (Journal of Sol-Gel Science and Technology, 2009)
Steam assisted dry gel conversion method was employed for the synthesis of Si-MCM-41 from ternary SiO2:CTAOH:H2O systems wherein fumed silica was used as a source of silica. The influence of synthesis time, molar ratios of CTAOH/SiO2 in dry gel and the water content at the bottom of autoclave on the quality and formation of mesophases has been investigated. Powder XRD, N-2 adsorption-desorption, TEM and hydrothermal stability test were the techniques used for sample characterization. Keeping molar ratio of CTAOH/SiO2 constant, shorter synthesis time, lower unit cell parameter and d spacing were observed when steam assisted dry gel conversion method was employed in place of conventional hydrothermal method. There exists an optimum lower limit for water content at the bottom of autoclave for reducing the synthesis period. Keeping synthesis temperature and CTAOH/SiO2 molar ratio fixed, Si-MCM-41 with improved hydrothermal stability was obtained by steam assisted dry gel conversion route.
Keywords: Dry gel conversion; powder diffraction; Si-MCM-41; Sol-gel growth; Structural stability; Textural properties